Unveiling the Potential: A Systematic Review on Harnessing the Affordances of Differentiated Instruction - Ramaila, Sam (Journal of Teaching and Learning, 2025)
Differentiated instruction stands as a cornerstone in modern pedagogical practices, aiming to cater to students' diverse needs and learning preferences. This systematic review delves into the vast landscape of differentiated instruction, aiming to illuminate its affordances and effectiveness across various educational settings. By synthesizing empirical evidence from many studies, this review examines the impact of differentiated instruction on student engagement, academic achievement, and overall classroom dynamics. Furthermore, it explores the implementation strategies, challenges, and best practices associated with harnessing the full potential of differentiated instruction. Through rigorous analysis, this review seeks to provide valuable insights for educators, policymakers, and researchers, guiding the enhancement of instructional practices and fostering inclusive learning environments. This systematic review demonstrated that differentiated instruction leads to increased student engagement. By tailoring instruction to meet the diverse needs of students, educators can better capture their interest and motivation. Additionally, this review highlights that differentiated instruction positively impacts learning outcomes. In essence, it underscores the role of differentiated instruction in promoting equity and inclusion in education. By recognizing and valuing the unique strengths and challenges of each student, it helps to create a more inclusive learning environment. These findings contribute to a broader understanding of the benefits, challenges, and best practices that are associated with differentiated instruction in educational settings.